2021
DOI: 10.3390/ma14051286
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Additive Firing on the Surface Characteristics, Streptococcus mutans Viability and Optical Properties of Zirconia

Abstract: The purpose of this study was to observe whether the repetitive firing of dental zirconia caused changes in surface characteristics, S. mutans viability, and optical properties of zirconia. Dental zirconia blocks were sintered and randomly distributed into seven experimental groups: F0-F6. Except for F0, which only went through sintering, the additive firing was performed in order for F1-F6. Surface roughness, contact angle, S. mutans viability by fluorescence, and translucency parameter were measured. They we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The repeated firings changed the translucency 0.5 mm thick specimens but had no significant effect on 1 and 1.5 mm thick specimens. TP values are decreased from 1 to 3 firings, while translucency is increased from 3 to 5 firings for all thickness specimens which is consistent with conducted by Moon et al [14] and Fathi et al [18].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The repeated firings changed the translucency 0.5 mm thick specimens but had no significant effect on 1 and 1.5 mm thick specimens. TP values are decreased from 1 to 3 firings, while translucency is increased from 3 to 5 firings for all thickness specimens which is consistent with conducted by Moon et al [14] and Fathi et al [18].…”
Section: Discussionsupporting
confidence: 90%
“…O'Brien et al [ 13 ] reported the perceivable color differences of specimens between 3rd and 5th firings. Firing processes can cause changes on optic and mechanical properties of the zirconia [ 14 ]. After repetitive firing procedures, differences in flexural strength, microhardness, and marginal fit can be seen in zirconia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Altan and Cinar 27) reported that multiple firing cycles decrease the translucency of zirconia. Several previous scholars have reported a significant decrease in translucency from the first to the third firing [27][28][29] . These results suggest that multiple firing cycles may decrease the translucency of highly translucent zirconia.…”
Section: Discussionmentioning
confidence: 86%